Mechanisms underlying human genetic diversity: consequence for antigraft antibody responses. (28th September 2017) - Reindl‐Schwaighofer, Roman; Heinzel, Andreas; Signorini, Lorenzo; Thaunat, Olivier; Oberbauer, Rainer
Summary: This review focuses on the emerging concept of genomewide genetic variation as basis of an alloimmune response. Chronic antibody‐mediated rejection is the major cause of long‐term graft loss and growing evidence supports the clinical relevance of HLA but also non‐HLA related alloimmune responses. Several polymorphic gene products have been identified as minor histocompatibility antigens. The formation of donor‐specific alloantibodies is driven by indirect allorecognition of donor‐derived peptides representing a form of conventional T‐cell response. With the availability of high‐throughput sequencing and genotyping technologies, the identification of genomewide genetic variation and thus mismatches between organ donors and graft recipients has become feasible. First clinical data linking genetic polymorphism and clinical outcome have been published and larger studies are currently under way. Protein arrays have successfully been used to identify a large variety of non‐HLA antibodies in kidney transplant recipients and the availability of customizable peptide arrays made screening for linear epitopes on an individual patient level feasible. This review provides a summary of the recent findings in histocompatibility matching in the field of solid organ transplantation and complements it with a clear workflow for assessing the impact of genetic differences in protein‐coding genes in solid organ transplantation.